Evaluation of Traditional Sorghum (Sorghum bicolor) Beer Residue, Shea-Nut (Vitellaria paradoxa) Cake and Cottonseed (Gossypium Spp) Cake for Poultry in Burkina Faso: Availability and Amino Acid Digestibility - Pousga, S.; Boly, H.; Lindberg, J.E.; Ogle, B. (International Journal of Poultry Science, 2007)
The present study aimed to evaluate the nutritive value for chickens of some local by-products in Burkina Faso and to estimate their true amino acid digestibility in cockerels. Sun-dried sorghum (Sorghum bicolor) beer residue (n = 144) and shea-nut (Vitellaria paradoxa) cake (n = 36) samples were collected in two different locations during six months, while cottonseed (Gossypium spp) cake samples were purchased monthly in a local market for the same period (n = 24). Mean Dry Matter (DM) content of beer residue was 94.7% and Crude Protein (CP), Ether Extract (EE), Crude Fibre (CF), Calcium (Ca), Phosphorus (P) and Metabolizable Energy (ME) contents were 23.4, 5.6, 8.5, 0.14 and 0.25% of DM and 13.4 MJ/kg, respectively. Mean lysine, methionine, cystine and threonine contents were 0.87, 0.44, 0.41 and 0.63%, respectively and the corresponding true excreta digestibility values were 92, 98, 95 and 97%. Mean DM content of shea-nut cake was 95.6% and CP, EE, CF, Ca, P and ME contents were 6.7, 7.3, 10.9, 0.40 and 0.19% and 13.1 MJ/kg, respectively. Lysine, methionine, cystine and threonine contents were 0.27, 0.14, 0.09 and 0.23% and the true digestibility values were 96, 78, 88 and 77%, respectively. Mean DM, CP, EE, CF, Ca, P and ME contents of cottonseed cake were 94.8, 44.3, 5.9, 9.9, 0.34 and 1.3% and 12.7 MJ/kg. Lysine, methionine, cystine and threonine contents were 1.6, 0.80, 0.82 and 1.9% and the true digestibility values were 89, 97, 98 and 94%. Overall, higher nutritive values were found for samples collected between October and December and no difference was found between locations.